DIGITAL-BASED PUBLIC RELATIONS MANAGEMENT IN ISLAMIC EDUCATIONAL INSTITUTIONS - Haris Maulana Safari; Musyarapah; Nurul Hikmah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
The rapid development of digital technology has significantly transformed educational management, particularly in school public relations (PR). This study aims to describe digital-based public relations management at SMP IT Al-Ghazali Palangka Raya, focusing on planning, organizing, and implementing digital communication programs. A descriptive qualitative approach was employed using interviews, observations, and documentation, with the principal and the head of public relations serving as key informants. The findings reveal that digital PR planning is conducted through annual coordination meetings with the foundation, monthly thematic planning, and collaborative weekly discussions. Organizationally, public relations management is structured through a clear division of roles among the principal, the PR coordinator, and a creative team responsible for digital content production. Implementation is carried out through various social media platforms, including Facebook, Instagram, YouTube, and TikTok, to strengthen two-way communication between the school and the community. The study concludes that digital public relations management at SMP IT Al-Ghazali Palangka Raya effectively builds a positive institutional image through adaptive and participatory communication grounded in Islamic values, such as wisdom (hikmah) and tabayyun, while highlighting the crucial role of principals’ digital literacy in sustaining technology-based innovation in Islamic education.